2019
DOI: 10.3389/fphar.2018.01531
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Metabolomics and Transcriptomics Reveals the Therapeutic Mechanism Underlying Paeoniflorin for the Treatment of Allergic Asthma

Abstract: Objectives: Asthma is a chronic airway inflammatory disease, which is characterized by airway remodeling, hyperreactivity and shortness of breath. Paeoniflorin is one of the major active ingredients in Chinese peony, which exerts anti-inflammatory and immune-regulatory effects in multiple diseases. However, it remains unclear whether paeoniflorin treatment can suppress allergic asthma.Methods: In this study, we evaluated the effect of paeoniflorin on lung function and airway inflammation in asthmatic mice. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…3A,B).We found that most of genes were related to the response to immune, Cancer immunotherapy is a breakthrough in cancer, such as cytokine therapy [34]. previous articles have con rmed the in ammation and immunity of paeoni orin in diseases such as rheumatoid [38], allergic asthma [39] and arthritis [40]. In addition, the GO analysis results also explain that paeoni orin is also involved in cell migration [17,41], cell activation, and cell activity regulation.…”
Section: Discussionmentioning
confidence: 54%
“…3A,B).We found that most of genes were related to the response to immune, Cancer immunotherapy is a breakthrough in cancer, such as cytokine therapy [34]. previous articles have con rmed the in ammation and immunity of paeoni orin in diseases such as rheumatoid [38], allergic asthma [39] and arthritis [40]. In addition, the GO analysis results also explain that paeoni orin is also involved in cell migration [17,41], cell activation, and cell activity regulation.…”
Section: Discussionmentioning
confidence: 54%
“…MetScape 3 may be used to visualize and interpret metabolomics and gene expression profiling data in an integrated metabolic network ( 28 , 30 ). To investigate the correlation of metabolites and gene expression affected by asarum treatment, metabolite and gene expression profiles were imported into the Cytoscape for Metscape analysis.…”
Section: Resultsmentioning
confidence: 99%
“…on diverse diseases such as rheumatoid arthritis, liver fibrosis, chronic heart failure, and asthma. [19][20][21][22] However, its efficacy against the development and progression of PAH has never been tested. In the present study, we found that paeoniflorin significantly ameliorated SU5416/hypoxia-induced PAH and reduced pulmonary vascular remodeling and right ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 99%